Developments in Corporate Governance Emerging Market Perspective - Kandpal, Vinay; Tripathy, Arun Kumar; Bisht, Nidhi S. (Approaches to Global Sustainability, Markets, and Governance, 2025)
XVI, 628 p. 55 illus., 45 illus. in color.